Analisis kecekapan relatif bagi industri saham amanah menggunakan pendekatan ekonometrik - Aleng @ Mohamad, Nor Azlida; Wan Ahmad, Wan Muhamad Amir; Mamat, Mustafa; Isa, Zaidi (Universiti Utara Malaysia, 2010)
Purpose – This paper measures the relative efficiency of unit trust in Malaysia for the year 2003 and 2004, consisting of 65 funds from 16 unit trust management company which are categorised into three types; growth fund, income fund, and Islamic fund. The importance of this study can help the investor/trustee to choose the most efficient fund. Design/Methodology/Approach – The study employed the production model by Battese and Coelli (1992). Frontier software Version 4.1 was used to analyse the efficiency score of unit trust funds and to estimate the parameters of stochastic production using maximum likelihood method.Findings – Score efficiency analysis is important to measure the level of technical efficiency in the unit trust industry and other industries. The growth fund showed increasing efficiency score when tested funds were categorised depending on the type or the investment objectives. The mean of efficiency score for the growth fund in 2003 is 95% and 99% in 2004. Entirely, the income fund in 2003 was more efficient than 2004 with 100% mean efficiency in 2003 and 93% in 2004. However, both funds were still considered as excellent and efficient.Meanwhile, the Islamic fund had low efficiency scores with 73% in 2003 and 84% in 2004. Originality/Value – The paper investigated extensively the relative efficiency and highlights these to investors, policy makers of unit trust, the unit trust industry and other industries.